2017
DOI: 10.1088/1757-899x/245/8/082025
|View full text |Cite
|
Sign up to set email alerts
|

Street as Public Space - Measuring Street Life of Kuala Lumpur

Abstract: Kuala Lumpur has envisioning in becoming World Class City by the year 2020. Essential elements of form and function of the urban environment are streets. Streets showcase the community and connect people. It's one of the most comfortable social environment that provides aesthetical and interaction pleasure for everyone. Classified as main shopping streets in the local Kuala Lumpur urban design guidelines, Jalan Masjid India (JMI) has its uniqueness of shopping experience and social interaction. This conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Such activities create a vibrant and liveable environment, promote users' sense of place and identity, and reflect the character of a good city (Al-Obeidy 2015; Ali et al 2019Ali et al , 2020 (Sipan et al 2021). Sulaiman et al, (2017) found that many visible activities take place along the streets, giving users a welcoming and vibrant feeling to enjoy and stay longer in streets (Mehta & Bosson 2018;Ping-Li Chen 2014;Sulaiman et al 2017;Zhu et al 2013).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Such activities create a vibrant and liveable environment, promote users' sense of place and identity, and reflect the character of a good city (Al-Obeidy 2015; Ali et al 2019Ali et al , 2020 (Sipan et al 2021). Sulaiman et al, (2017) found that many visible activities take place along the streets, giving users a welcoming and vibrant feeling to enjoy and stay longer in streets (Mehta & Bosson 2018;Ping-Li Chen 2014;Sulaiman et al 2017;Zhu et al 2013).…”
Section: Research Backgroundmentioning
confidence: 99%
“…From the observation, the community here is conditioned to the physical condition and shapes their psychological development, therefore a change to this condition will take a lot of hard work. In an urban environment, the elements that complete the form and function of it are streets, and the role of the street is only seen to be the major thoroughfare for vehicular traffic (Sulaiman et al, 2017). In the context of Kuala Lumpur and the people's housing scheme, this is a real sight where the volume of the vehicles and the density of living condition is at balance, and this is not good.…”
Section: Physical and Psychological Developmentmentioning
confidence: 99%
“…Therefore a change to this condition will take a lot of hard work. In an urban environment, the elements that complete the form and function of it are streets, and the role of the road is only seen to be the major thoroughfare for vehicular traffic (Sulaiman et al, 2017). In the context of Kuala Lumpur and the people's housing scheme, this is a real sight where the volume of the vehicles and the density of living condition is at balance, and this is not good.…”
Section: Physical and Psychological Developmentmentioning
confidence: 99%